Analisis Kualitas Website Tokome Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis - Devitasari, Devitasari; Wati, Theresia; Sarika, Sarika (Jurnal Informatika Universitas Pamulang, 2021)
Tokome.id is an e-commerce company that provides merchandise manufacturing services by sending a design image of the product that we want to buy or sell. The purpose of this research is to measure the quality of the website owned by Tokome.id. To see the quality of a website, it is necessary to measure based on the quality based on the users using Webqual 4.0 method which consists of 3 variables (usability, information quality, service interaction quality), and 22 question indicators. The technique used by researchers is Importance Performance Analysis (IPA) method which provides an overview of what indicators need improvement or needs to maintain their quality based on user perceptions and expectations. Based on the results of the analysis of Importance Performance Analysis (IPA), it shows that the 22 items analyzed using the importance-performance analysis method are divided into quadrant I (8 items), quadrant II (6 items), quadrant III ( 5 items), and quadrant IV (3 items). Items that are considered very important and need to be improved are in quadrant I, namely the sense of data or information security when accessing the website. These outcome show that the quality of the Tokome. id website is still lacking and has not met user expectations.